2013
DOI: 10.3389/fpls.2013.00258
|View full text |Cite
|
Sign up to set email alerts
|

Investigating the beneficial traits of Trichoderma hamatum GD12 for sustainable agriculture—insights from genomics

Abstract: Trichoderma hamatum strain GD12 is unique in that it can promote plant growth, activate biocontrol against pre- and post-emergence soil pathogens and can induce systemic resistance to foliar pathogens. This study extends previous work in lettuce to demonstrate that GD12 can confer beneficial agronomic traits to other plants, providing examples of plant growth promotion in the model dicot, Arabidopsis thaliana and induced foliar resistance to Magnaporthe oryzae in the model monocot rice. We further characterize… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
80
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 100 publications
(89 citation statements)
references
References 77 publications
3
80
0
Order By: Relevance
“…In particular this result has been noted in terms of root growth promotion, although significant increases have also been observed in aboveground vegetative growth such as stem length and thickness, leaf area, chlorophyll content and yield (size and/or number of flowers and/or fruits) [5,13,21,27,77]. Numerous hypothesis have been proposed to explain this observation including the improvement of chemical solubilisation, sequester, availability (i.e.…”
Section: Introductionmentioning
confidence: 90%
See 1 more Smart Citation
“…In particular this result has been noted in terms of root growth promotion, although significant increases have also been observed in aboveground vegetative growth such as stem length and thickness, leaf area, chlorophyll content and yield (size and/or number of flowers and/or fruits) [5,13,21,27,77]. Numerous hypothesis have been proposed to explain this observation including the improvement of chemical solubilisation, sequester, availability (i.e.…”
Section: Introductionmentioning
confidence: 90%
“…Modern scientific technology provides the possibility to conduct pre-field selection for suitable BCAs based on various studied genetic and biochemical characters known to be involved in the biological processes important and useful for crop protection. Screening is performed on the microorganism extracts by using high throughput screening, analysis of the proteome, metabolome transcriptome and other 'omics, microbiome and metagenomic analysis of "stimulating" plant-microbe environments, whole genome next generation sequencing [6,8,77,101,102]. Based on known desirable characteristics, new strains can be designed and developed by using hybrid technology (i.e.…”
Section: Introductionmentioning
confidence: 99%
“…Trichoderma hamatum T382 induced systemic resistance against Botrytis cin erea in Arabidopsis thaliana which involved the triggering of defense enzymes, including glucanases, chitinases and other pathogenesis related proteins of the SA and Et-pathways (Mathys et al 2012). The ability of T. hamatum strain GD12 to elicit systemic resistance against Magnaporthe oryzae in rice, and S. scle rotiorum in lettuce was traced to its unique genomic regions with the potential to encode novel bioactive metabolites such as defense enzymes and proteins (Studholme et al 2013). Mayo et al (2015) recorded up regulation of seven defense related genes including glucanase during Trichoderma induced resistance against Rhizoctonia solani in beans.…”
Section: Discussionmentioning
confidence: 99%
“…Over the last decade, there has been an increasing demand in the agricultural market for biological agents that work with similar or possibly better efficacy than chemical agents at defending against a wide range of plant pathogens (Yedidia et al, 1999;Harman et al, 2004).Consequently, the search for Trichoderma species with high antagonistic potential against plant pathogens has become more attractive in recent years for the development of environment friendly agricultural practices. Recently, T. hamatum has gained interest in both academia and industry for its ability to enhance a plant's biomass and control pathogenic fungi (Studholme et al, 2013). This species' efficient control of plant pathogens depends on several physiological properties such as a rapid growth rate, ability to utilize various substrates, resistance to noxious chemicals, and production of antibiotics and extracellular hydrolytic enzymes (Carsolio et al, 1994;Lorito et al, 1996a, b;Kullnig et al, 2000;Harman et al, 2004;Chase and Fay, 2009;Studholme et al, 2013).…”
Section: Introductionmentioning
confidence: 99%
“…Recently, T. hamatum has gained interest in both academia and industry for its ability to enhance a plant's biomass and control pathogenic fungi (Studholme et al, 2013). This species' efficient control of plant pathogens depends on several physiological properties such as a rapid growth rate, ability to utilize various substrates, resistance to noxious chemicals, and production of antibiotics and extracellular hydrolytic enzymes (Carsolio et al, 1994;Lorito et al, 1996a, b;Kullnig et al, 2000;Harman et al, 2004;Chase and Fay, 2009;Studholme et al, 2013). Wang et al (2013) showed that T. hamatum could restrict the growth of bacterial wilt pathogens in ginger.…”
Section: Introductionmentioning
confidence: 99%